Development of proxy relationships: a case study of the Lebanese Civil War. (3rd July 2016) - Sozer, Brendan
Abstract: Proxy warfare is a consistent element in international warfare. However, it is unclear why proxy relationships form in cases where states have multiple options of groups to support. Existing research identifies the presence of transnational constituencies, shared interstate rivalries, and moderate relative strength of militant groups as highly influential on the development of a proxy relationship. This study examines the presence of these variables within the context of the Lebanese Civil War. The results of this demonstrate that each state places greater importance on some variables and ignores others when choosing a proxy. Additionally, this study further demonstrates the presence of new variables that are key to the development of proxy relationships.